Analysis and Application of Access Control List (ACL) Methods on Computer Networks - Fadhil Azmi; Toibah Umi Kalsum; Hendri Alamsyah (Jurnal Komputer, Informasi dan Teknologi, 2022)
Advances in information technology are currently growing to meet the needs of humans who want to obtain information easily, quickly and precisely. Therefore, we must continue to pursue and improve the quality and quantity of information technology. The purpose of this study is to find out how to perform the analysis and application of the Access Control List (ACL) method in a computer network. Mikrotik RB750 router is good to use for network security both in terms of reliability and in terms of cost. The method of network security using a firewall and address list is good because it can perform network security and restrictions on addresses that can be accessed and cannot be accessed. With this computer network security, computer network users can get internet access and local network access that is stable and smooth.